2019
DOI: 10.1016/j.pec.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of self-disclosure by peer mentors: Using personal narratives in depression care

Abstract: Objective: Self-disclosure is recognized as an important aspect of peer support, but little is known about its use by peers. This study aimed to qualitatively understand peer self-disclosure in the context of depression care delivery to older adults. Methods: 69 audio-recordings of peer-client meetings were coded for self-disclosure using the Roter Interaction Analysis System (RIAS). Peer self-disclosure was defined as a statement describing personal life experience with physical and/or emotional relevance for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Research had revealed that QOL had become an important outcome measure in breast cancer clinical research and survival research, and could be used as a predictor of mortality rate in breast cancer survivors [7] . Research had shown that patients with breast cancer after surgery generally experienced stigma, which had an adverse impact on the QOL of patients [8][9][10] , and patients' self-disclosure and social support could improve the QOL, which had a positive impact [11][12][13] . In conclusion, the purpose of this study is to investigate the relationship among stigma, self-disclosure, social support, and QOL in breast cancer patients after surgery, and to construct the chain mediation model of self-disclosure and social support.…”
Section: Backgroundsmentioning
confidence: 99%
“…Research had revealed that QOL had become an important outcome measure in breast cancer clinical research and survival research, and could be used as a predictor of mortality rate in breast cancer survivors [7] . Research had shown that patients with breast cancer after surgery generally experienced stigma, which had an adverse impact on the QOL of patients [8][9][10] , and patients' self-disclosure and social support could improve the QOL, which had a positive impact [11][12][13] . In conclusion, the purpose of this study is to investigate the relationship among stigma, self-disclosure, social support, and QOL in breast cancer patients after surgery, and to construct the chain mediation model of self-disclosure and social support.…”
Section: Backgroundsmentioning
confidence: 99%
“…Such stories are often referred to in research and practice as ‘recovery narratives’ ( Kerr et al, 2020 ; Llewellyn-Beardsley et al, 2019 ; Mancini, 2019 ; Piat et al, 2019 ), and interest in them has increased within services in tandem with the global adoption of a recovery paradigm by healthcare policy and practice ( Nettleton, 2020 ). Their use has become widespread in services for diverse purposes, including within staff training to improve service delivery and increase empathy ( Salter & Newkirk, 2019 ); public health campaigns and living libraries to challenge stigma ( González-Sanguino et al, 2019 ; Kwan, 2020 ); online interventions to increase access to self-care resources ( Slade et al, 2021 ; Williams et al, 2018 ); and as a distinctive feature of peer support ( Moran et al, 2012 ; Truong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…6 Self-disclosure has health benefits, it can enhance an individual’s positive self-perception, and increases the ability to regulate emotions. 8 Previous studies have shown that self-disclosure can also be used for self-care in older adults, 9 improving subjective well-being and quality of life. Furthermore, self-disclosure was found to be able to reduce psychological distress by changing self-perception to a more resilient condition.…”
Section: Introductionmentioning
confidence: 99%